Building collaborative leadership: A qualitative evaluation of the Australian Collaborative Pairs trial. (2nd September 2020) - Dickinson, Helen; Brown, Alison; Robinson, Suzanne; Parham, Jenny; Wells, Leanne
Abstract: The need to reorient the health system to ensure greater involvement of consumers in healthcare has, in recent years, been highlighted as a priority in both literature and policy. This change requires renegotiating power relations among health organisations, health professionals and health consumers. This study presents findings from a trial of a program designed to foster collaborative relationships between clinicians and consumers of health services in the Australian setting. The King's Fund Collaborative Pairs program is a leadership development program that brings together a consumer, patient or community leader to work together in pairs with a service provider clinician or manager to develop new ways of working together. The trial involved 88 participants paired together undertaking one of seven programs conducted from October 2018 to August 2019. Participants were guided through a series of activities in five face‐to‐face sessions run by facilitators trained by the King's Fund. A qualitative evaluation was undertaken via semi‐structured interviews ( n = 40) with organisations involved, facilitators and participants. A brief review of program documentation was also included. Thematic analysis was undertaken to evaluate program acceptability, implementation and to identify program impacts. The evaluation, although limited in scope, found the program changed the way some participants understood the nature of consumer and provider relationships and how collaborative working relationships could be developed. The impact of the program on organisations sponsoring participants was less evident as numbers of participants from each organisation were limited and the time required for cultural change to develop is typically longer than the evaluation period allowed for. We highlight key recommendations addressing program recruitment, facilitation and format to inform future iterations of the program.